2012
DOI: 10.3109/00365599.2011.649045
|View full text |Cite
|
Sign up to set email alerts
|

Does stage III chronic kidney disease always progress to end-stage renal disease? A ten-year follow-up study

Abstract: About half of the patients with stage 3 CKD progressed to stage 4 or 5, as assessed by eGFR, over 10 years. Degree of albuminuria, stage 3 subgroup and microscopic haematuria were important risk factors for progression of stage 3 CKD. It would be appropriate to divide the present stage 3 CKD into two subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 23 publications
3
29
0
2
Order By: Relevance
“…it is a late marker of disease progression. Moreover, many CKD patients in the G3a category 1,7 , the most prevalent CKD category, never progress, as recently observed for a classical albuminuric disease such as diabetic nephropathy. Although UAE is clinically useful to stratify risk, in some patients there are discrepancies between the urinary albumin creatinine ratio and 24h UAE 8 .…”
Section: Introductionmentioning
confidence: 63%
“…it is a late marker of disease progression. Moreover, many CKD patients in the G3a category 1,7 , the most prevalent CKD category, never progress, as recently observed for a classical albuminuric disease such as diabetic nephropathy. Although UAE is clinically useful to stratify risk, in some patients there are discrepancies between the urinary albumin creatinine ratio and 24h UAE 8 .…”
Section: Introductionmentioning
confidence: 63%
“…A systematic review has shown that the mortality rate of the patients with Stage 3 CKD is higher than those without CKD [28]. Another review has shown that half of the patients suffering from Stage 3 CKD have progressed to Stage 4 and Stage 5 over 10 years [29]. Eventually, these patients will need renal replacement therapy and kidney transplantation in near future.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers including an abnormal ankle-brachial index (ABI), arterial stiffness, increased common carotid artery (CCA) diameter and intima-media thickness (CIMT), and left ventricular hypertrophy (LVH) are associated with increased cardiovascular risks and worse prognosis in CKD (Szeto et al, 2007;Chue et al, 2010;Paoletti et al, 2011;Karras et al, 2012;Kozakova et al, 2017;Chen et al, 2017;Major et al, 2018). Moreover, most of the studies of mildto-moderate CKD have evaluated the deterioration of renal function over time (Baek et al, 2012;Hallan et al, 2012), and few have addressed the longitudinal changes in biomarkers associated with cardiovascular risk (Seifert et al, 2014;Agarwal, 2017). Moreover, most of the studies of mildto-moderate CKD have evaluated the deterioration of renal function over time (Baek et al, 2012;Hallan et al, 2012), and few have addressed the longitudinal changes in biomarkers associated with cardiovascular risk (Seifert et al, 2014;Agarwal, 2017).…”
Section: Introductionmentioning
confidence: 99%